Determinants Influencing Firm’s R&D Collaborations With Universities: Empirical Evidence From Europe - Odei, Samuel Amponsah (Academic Conferences and Publishing International Limited, 2018)
Universities have long remained the hub of scientific research and training of the manpower base of countries. But in recent times there have been a paradigm shift in these roles played by universities, there are increasing calls for them to directly contribute to regional and economic growth and forging closer and direct collaborations with industries and commercializing their academic research outcomes. This institutional interdependence results in win-win outcomes for both industries and universities. Universities interact with industries through diverse means such as joint research and development, staff and student mobility, academic consulting, joint publication of academic papers among others. Technology intensive industries need the most sophisticated technology and knowledge to thrive. Greater attention has been paid to this collaboration, but little is known about which universities firms collaborate with. The main aim of this paper therefore is to empirically observe factors that influence technology intensive industries choice of universities (domestic or foreign) as collaborating partners across European Countries. These determinants included firm size, innovation expenditures, availability of funding and the extent of internationalization. For the empirical analysis, we used data from the Community Innovation Survey 2010-2012 and the standard logit regression model. The results of the logit regression demonstrated statistically that firm size, innovation activities and funding influenced firm’s collaboration with local universities. Per contra, the results revealed insignificant differences for foreign universities
Determinanty ovlivňující vědecko-výzkumnou spolupráci firem s univerzitami - Evropská empirická studie
Keywords: Firm’s R&D Collaborations; Universities; Europe; vědecko-výzkumná spolupráce; firmy; univerzity; Evropa